Effects of thermo-photoperiod on induction and termination of hibernation in Chilo partellus (Swinhoe). Issue 3 (10th November 2016) - Dhillon, M. K.; Hasan, F.; Tanwar, A. K.; Bhadauriya, A. S.
Abstract: Determination of critical threshold for induction and termination of diapause (hibernation) are important for better understanding the bio-ecology and population dynamics of Chilo partellus (Swinhoe) under varying climatic conditions. We studied initiation and termination of hibernation under five temperature and photoperiod regimes viz., 27°C + 12L:12D, 22°C + 11.5L:12.5D, 18°C + 11L:13D, 14°C + 10.5L:13.5D and 10°C + 10L:14D under fixed and ramping treatments, and the observations were recorded on various phenological and developmental characteristics at weekly intervals. Present studies revealed that the induction of hibernation in C. partellus larvae takes from 46 to 56 days depending upon temperature and photoperiod conditions. Induction of hibernation varied from 7.9 to 18.3% across treatment conditions, indicating that not all C. partellus larvae undergo diapause under prevailing environmental conditions. Weight, length and head capsule width of diapausing larvae were found significantly lower than the non-diapausing larvae. The non-diapausing C. partellus larvae required a thermal threshold of 1068 degree-days under ambient conditions, while in case of hibernating larvae it varied significantly across treatment conditions. Diapausing larvae underwent up to five supernumerary moults, wherein highest percentage of diapausing larvae (35.7%) exhibited two supernumerary moults. The developmental time of diapausing larvae varied from 94.9 to 160.4 days across treatments. A population loss of 17.2–28.3% was recorded in C. partellus due to hibernation, which has implications for population buildup of post-hibernation first brood and management strategies.